OrpR is a σ54-dependent activator using an iron-sulfur cluster for redox sensing in Desulfovibrio vulgaris Hildenborough - Fiévet, Anouchka (2021)
SFCT‐ANR/BBB‐MET/0023/2012 IAP7/44, iPROS project) COST Action CA15133